2016
DOI: 10.1177/1461444816645652
|View full text |Cite
|
Sign up to set email alerts
|

Using social media to enhance citizen engagement with local government: Twitter or Facebook?

Abstract: The social media are becoming a major channel of online interactive participation, and local governments are seizing this opportunity to enhance citizen engagement in political and social affairs. This article analyses the various forms of social media used – that is, Twitter or Facebook – by citizens in their relations with Spanish local government, to determine which of these achieves the strongest degree of commitment. We also analyse the influence of various factors on this level of commitment. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
14

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(165 citation statements)
references
References 51 publications
(120 reference statements)
6
145
0
14
Order By: Relevance
“…All data related to messages containing the word ‘Syria’ sent by local governments and NGOs via Facebook were extracted during the analysis period (1 May 2015–31 December 2016). Facebook was chosen because it is the most suitable application for online citizen engagement (Haro‐de‐Rosario, Sáez‐Martín, and Caba‐Pérez, ).…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…All data related to messages containing the word ‘Syria’ sent by local governments and NGOs via Facebook were extracted during the analysis period (1 May 2015–31 December 2016). Facebook was chosen because it is the most suitable application for online citizen engagement (Haro‐de‐Rosario, Sáez‐Martín, and Caba‐Pérez, ).…”
Section: Methodsologymentioning
confidence: 99%
“…A multivariate regression model was employed to investigate the relation between certain factors in the responses of citizens via SM with regard to the Syrian refugee crisis, in line with other similar analyses of SM in the public sphere (Haro de Rosario, Sáez-Martín, and Caba-Pérez, 2016). With respect to the second objective set out above, the dependent variable selected was the type of response message.…”
Section: Explicative Analysis: Influencing Factors In Online Responsesmentioning
confidence: 99%
“…Secondly, scholars have extensively studied the influences of content type (Bhattacharya et al, 2017;Bons� on et al, 2015Bons� on et al, , 2019; Bons� on & Bedn� arov� a, 2018; Lee & Xu, 2018;Rahim et al, 2019;Tang et al, 2019), multimedia feature (Bhattacharya et al, 2017;Bons� on et al, 2015Bons� on et al, , 2019Lee & Xu, 2018;Rahim et al, 2019), emotions (Bhattacharya et al, 2017;Haro-de-Rosario, S� aez-Martín, & delCarmen Caba-P� erez, 2018;Tang et al, 2019;Zavattaro et al, 2015), del Mar G� alvez-Rodríguez et al, 2018;Haro-de-Rosario et al, 2018) on CEGSM. Only one study by del Mar G� alvez-Rodríguez et al (2018) employed the DCT to investigate citizen engagement through the Facebook accounts of local Latin American governments; their results confirmed that the generation of new visits, dialogic loop and information of interest to stakeholders, which belongs to the principles of DCT, promotes citizen engagement (the weighted statistics of likes, shares, comments and posts).…”
Section: Citizen Engagement Through Government Social Mediamentioning
confidence: 99%
“…Currently, however, social media has become a major channel for online interactive participation, and local governments are seizing this opportunity to enhance citizen engagement in political and social affairs (Haro-de-Rosario, Sáez-Martín, & del Carmen Caba-Pérez, 2018). Given the importance of citizen engagement, or the participation of citizens in political and social affairs, research has shown that productive use of social media by government agencies can enhance citizen engagement and confidence in the government.…”
Section: Introductionmentioning
confidence: 99%